Technology management in University Library (Confluenţe Bibliologice, 2013)
In order to ensure the eﬃcient functionality of the library is needed to provide a modern technological management: application of contemporary methods, forms and new methods of analysis, evaluation and implementation of new technologies, improvement of technological processes and operations, optimizing the technological potential, reasonable modiﬁcation of the informational technologies.
Keywords: library management; library services